How were the Online Classes in Undergraduate Medical Teaching during COVID Pandemic? Students’ Views of a Non-Government Medical College in Bangladesh - Khanom, Mehrunnissa; Hoque, Afroza; Sharif, Parvez Iqbal; Sabuj, Muslim Uddin; Hossain, Md Amir (Bangladesh Journal of Medical Education, 2020)
Abrupt closure of educational institutions due to COVID pandemic had created historical impact on educational system all over the world, the situation had been more challenging in undergraduate medical teaching. Moving smoothly from an environment of conventional education to virtual platform could not happen overnight. The current paper presents results of a cross-sectional study conducted from 13th July to 20th July, 2020 on MBBS students of Chattagram International Medical College, a non-Government Medical College of Bangladesh, exploring students’ views on online classes. A total of 217 students participated in the study, the response rate of survey was 87%. Among pre-clinical students, 47.6% ±1.1% and among clinical students 48.3% ±0.8% ‘sometimes’ felt interested in the class. Though majority of both pre-clinical and clinical students mentioned having appropriate device; there had been a wide range of variations in responses regarding their own internet connectivity. The most striking finding came out with the question if online class would be felt as a good substitute of ‘face-to-face’ class; it was ‘never’ response in more than 70% students in both pre-clinical and clinical groups. To take challenge of creating real-life picture in online class, there is necessity of a shift of traditional ‘lecture-based ’classes to more interactive, simulation-based classes; specially for clinical students. Institutional support needs to be strengthened for ensuring sound and visibility during the classes. Bangladesh Journal of Medical Education Vol.11(2) 2020: 3-13